Biochemistry of Hair Greying: A Review - Austin-Amadi, Wendy Chinenye; Joseph, Guzol Joy; Terhide Samuel, Tyohemba; Danjuma, Yakubu; Kitime Jonah, Joyous Wilson; Abdullahi, Ladan; Hamza, Hajjagana (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
Hair greying is a natural biological process influenced by genetics, aging, and environmental factors. This phenomenon occurs when melanocytes, specialized cells responsible for melanin production, lose functionality, leading to a decline in melanin synthesis. Melanin, comprising eumelanin and pheomelanin, is the pigment that determines hair color. The greying process involves oxidative stress, a gradual reduction in melanocyte activity, and depletion of melanocyte stem cells, resulting in diminished melanin production. Genetic factors, such as mutations in the MC1R and IRF4 genes, further modulate the greying process. In addition to age-related factors, lifestyle influences, including smoking and nutrient deficiencies (e.g., vitamin B12 and trace elements), play significant roles in premature greying. Oxidative stress, in particular, accelerates melanocyte apoptosis and contributes to hair greying by increasing reactive oxygen species (ROS) levels, which damage cellular structures. While the treatment of age-related greying remains elusive, some cases of premature greying can be managed through dietary supplements and lifestyle adjustments. This study aims to elucidate the biochemical pathways of hair greying, explore potential therapeutic interventions, and highlight the environmental and genetic factors that contribute to the process.